Is Stryd critical power a meaningful parameter for runners? - Dearing, C. G.; Paton, C. D. (Biology of Sport, 2023)
Stryd is a foot pod that reliably estimates running power. Our objectives were to examine the efficacy of the website-generated Stryd critical power (CPSTRYD) as a meaningful parameter for runners. 20 runners performed their regular training while wearing Stryd for a minimum of 6 weeks to generate CPSTRYD. Runners completed laboratory graded exercise testing, and outdoor 1500 m and 5000 m time trails. CPSTRYD was most similar to the second ventilatory threshold (VT2) or the onset of blood lactate accumulation (OBLA) and is highly predictive of running performance. Stryd ground contact time (GCT) was a predictor of performance when comparing runners at the same submaximal treadmill speed. CPSTRYD generated from outdoor running is equivalent to that calculated using an established CP model. However, variance between different methods of CP estimation must be a consideration for runners and coaches. Stryd offers meaningful data for runners including a realistic estimate of CP.